Frühneuhochdeutsche Register mündlicher Kommunikation in Olmützer Prozessakten von 1550 bis 1630 - Spáčilová, Libuše (. Studia Germanistica. - Ostrava : Ostravská univerzita v Ostravě, [2009]-. - Online-Ressource. - ISSN 2571-0273 23, 2020)
One of the significant fields of institutional communication in the Early New High German period was the legal system. It can therefore be assumed that court documents from that era include elements of the contemporary spoken language. This paper presents the results of a corpus analysis examining 40 examples of two text types in court documents - witness accounts and testimonies of men tortured on the rack. Elements of the spoken language were found on the phonetic/phonological, morphological and syntactic/textual levels.